The Stream of Consciousness of Exiled Characters in the Novel Pulang by Leila S. Chudori: A Direct, Free Discourse Analysis - Kartika Amalia Neno; Herman Didipu; Zilfa Achmad Bagtayan (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to analyze free direct discourse as a representation of exile characters’ stream of consciousness in Leila S. Chudori’s novel Pulang using a pragmatic stylistics approach. Grounded in Elizabeth Black’s (2016) framework, the research addresses three objectives: (1) to identify the forms of free direct discourse in the novel, (2) to examine its pragmatic functions in representing the psychological conditions of exile characters, and (3) to interpret its stylistic implications for reading historical trauma and identity crises. Employing a qualitative descriptive-analytical method, data were collected purposively from the novel based on Black’s linguistic criteria. Out of 33 identified instances, three representative excerpts were selected for in-depth analysis using qualitative content analysis, pragmatic interpretation, and stylistic evaluation. The findings reveal three primary forms of free direct discourse: (1) chained rhetorical questions that depict existential confusion and fragmented cognition; (2) expressions of astonishment and disbelief that articulate the absurdity of exile and function as existential protest; and (3) reflective criticism of official historical narratives that demonstrate mature critical awareness. Pragmatically, these forms operate as narrative strategies that authentically reconstruct traumatic memory, foster emotional immediacy with readers, and serve as subtle ideological critiques against historical repression and collective amnesia. A systematic psychological gradation—from confusion and shock to critical reflection—indicates that free direct discourse also mirrors the characters’ gradual psychological recovery. This study contributes to the development of pragmatic stylistics in contemporary Indonesian fiction and offers a linguistic lens for reading historical trauma through narrative form.